GENEALOGY, DIASPORA, AND DA’WAH: The Religious Role of Sheikh Ibrahim al-Hadhrami in Pattani and Java - Muaz Tanjung; Arik Dwijayanto; Nabil Chang-Kuan Lin (AL-TAHRIR, 2021)
Abstract: There are several problems in the historiography of Islam Nusantara nowadays. One of them is the lack of written sources, especially during the XIV-XV centuries. It was a significant period when the early generation of preachers (Walisongo) played a significant role in spreading Islam in the archipelago. Because of the limitations of written sources, some scholars assume Walisongo as a myth. This article aims to reveal the genealogy, sanad, and religious roles of one of the early Walisongo, Shaykh Ibrahim al-Hadrami, in Pattani and Java. This study applied historical research methods. It relied on critical testing and analysis, including heuristics, verification, interpretation, and historiography. Besides, the findings showed the continuity of the genealogy and sanad of Shaykh Ibrahim al-Hadrami and his descendants. They formed a network of Ulama and da’wah centers in Pattani and Java. In Pattani, Islamic preaching centers built by Sheikh Ibrahim al-Hadrami were continued by his descendants, such as Sheikh Ahmad bin Muhammad Zain al-Fathani and Sheikh Daud al-Fathani. They developed in Kedah, Kelantan, and several areas in the Malay Peninsula. Meanwhile, in Java, the centers of Islamic da’wah built by Sheikh Ibrahim al-Hadrami were continued by his two sons, Raden Rahmat (Sunan Ampel) and Raden Ali Murtadla (Sunan Gresik) and their descendants. Therefore, Islam developed throughout Java.الملخص : بعض مشاكل التاريخ الإسلامي في الأرخبيل لا تزال تطفو على السطح حتى الآن. منها، أنّ المصادر المكتوبة غير متوفّرة. خاصّة في القرن XV-XIV رغم أنّ تلك الفترة، فترة مهمّة حيث يلجأ الجيل  المبكّر من الدواعي (والي سونغو) دوراً هامّاً في نشر الإسلام في الأرخبيل. بعض العلماء يعتبرون والي سونغو أسطورة، لأنّ المصادر المكتوبة محدودة. للمساهمة في الدراسة القائمة، تهدف هذه المادّة إلى الكشف عن الأنساب والسند والدور الديني من أحد الجيل الأوّل من والي سونغو – الشيخ إبراهيم الحضرمي-  في باتاني وجاوى. تستخدم هذه الدراسة طرق البحث التاريخية التي تعتمد على الاختبار والتحليل النقدي بما في ذلك الاستدلال والتحقّق والتفسير والتأريخ. تظهر هذه الدراسة استمرارية أنساب وسند الشيخ إبراهيم الحضرمي وذريته الذين يشكلون شبكة من مراكز العلماء والدعوة في باتاني وجاوى. في باتاني، استمرّت مراكز الدعوة الإسلامية التي بناها الشيخ إبراهيم الحضرمي من قبل ذريته مثل الشيخ أحمد بن محمّد زين الفتحاني والشيخ داوود الفتحاني الذي تطوّر في كيدا وكلنتان وعدّة مناطق في شبه جزيرة الملايو. وفي نفس الوقت، استمرّت مراكز الدعوة الإسلامية في جاوى التي بناها الشيخ إبراهيم الحضرمي من قبل ولديه، رادين رحمة (سونان أمبل) ورادين عليّ مرتضى (سونان جريسيك) وذريتهم، حتى تطوّر الإسلام في جميع أنحاء جاوى.Abstrak: Beberapa permasalahan dalam historiografi Islam Nusantara sampai saat ini masih terus mengemuka, salah satunya adalah kurangnya sumber tertulis, khususnya masa abad XIV-XV. Padahal masa tersebut merupakan masa yang sangat penting dimana generasi awal para pendakwah (Walisongo) memainkan peranan signifikan dalam menyebarkan Islam di Nusantara. Keterbatasan sumber tertulis menjadikan sebagian cendekiawan menganggap Walisongo sebagai mitos. Untuk berkontribusi pada studi yang ada, artikel ini bertujuan untuk mengungkap silsilah, sanad dan peran keagamaan salah satu Walisongo generasi awal, yakni Syaikh Ibrahim al-Hadrami di Pattani dan Jawa. Penelitian ini menggunakan metode penelitian sejarah yang bertumpu pada pengujian dan analisis kritis meliputi heuristik, verifikasi, interpretasi, dan historiografi. Kajian ini menunjukkan ketersambungan silsilah dan sanad Syaikh Ibrahim al Hadrami serta keturunannya yang membentuk jejaring Ulama dan sentra-sentra dakwah di Pattani dan Jawa. Di Pattani, sentra-sentra dakwah Islam yang dibangun Syaikh Ibrahim al-Hadrami dilanjutkan oleh keturunannya, seperti Syaikh Ahmad bin Muhammad Zain al-Fathani and Syaikh Daud al-Fathani yang berkembang di Kedah, Kelantan dan beberapa kawasan di Semenanjung Melayu. Sedangkan di Jawa, sentra-sentra dakwah Islam yang dibangun Syaikh Ibrahim al-Hadrami dilanjutkan oleh kedua putranya, Raden Rahmat (Sunan Ampel) dan Raden Ali Murtadla (Sunan Gresik) beserta keturunannya sehingga Islam berkembang diseluruh wilayah tanah Jawa.